The Network Structure of Trauma Symptoms of Abuse-exposed Children and Adolescents in South Africa - Makhubela, Malose (Journal of interpersonal violence, 2022)
Network theory promises new ways for conceptualizing, methods for investigating, and state-of-the-art lines of research that will improve our knowledge of mental health in high-risk children and adolescents. This study constructed a symptom network to examine associations between a wide range of trauma symptoms in a sample of children and adolescents (N = 270; Mage = 12.55 yrs, SD = 1.19; 67% = Female) who experienced different forms of abuse (i.e., sexual, physical, emotional and neglect). Symptom-pairs regularized partial correlations, with the Extended Bayesian Information Criterion Graphical Least Absolute Shrinkage and Selection Operator (EBICglasso), were computed to estimate the network structure and centrality measures of the TSCC-SF items. Results show sadness, dissociative amnesia, and sexual arousal to be the most central symptoms in the network, while suicidality was found to be the shortest pathway across all other symptoms (domains). By providing clinicians with specific symptoms to target in interventions, the network framework has the potential to guide and enhance the effectiveness of psychological therapies in high-risk populations.